Competency of Human Resources and Customer Trust on Customer Satisfaction and Its Consequence on Customer Retention in the Hospitality Industry North Sumatra - ANWAR, Yohny; FERINE, Kiki Farida; SIHOMBING, Nikous Soter (Journal of Environmental Management and Tourism, 2020)
This research was carried out by of the hospitality industry in North Sumatra. The object of this research is human resource competency, customer trust, customer satisfaction and customer retention in the North Sumatra hospitality industry. The Outcome of this study indicates that human resource competence, customer trust, customer satisfaction and customer retention in the hospitality industry in North Sumatra, Indonesia is relatively good. Human resource competency has an Consequence on customer satisfaction. Customer trust Consequences customer satisfaction. Human resource competency has a Consequence on customer retention. Customer trust has a significant Consequence on customer retention. In addition, there is a Consequence of customer satisfaction on customer retention and there are direct and indirect Consequences of human resource competence and customer confidence in customer satisfaction as well as a Consequence on customer retention of the hospitality industry in North Sumatra.